The design process - Aspelund, Karl. (London ; New York : Fairchild Books, an imprint of Bloomsbury Publishing Inc., 2015)
"Karl Aspelund takes readers on a guided tour of seven stages of design, from Inspiration, Identification, Conceptualization, Exploration/Refinement, Definition/Modeling, Communication and Production. New cumulative storyboards of three different types of designs (graphics, clothing, and web design) progress through each stage to show how each setp is implemented in practical application. "Perspectives" features highlight individual designers and artists, and end-of-chapter exercises help transform design projects to reality"--
Includes bibliographical references and index.
Keywords: Design -- Methodology; DESIGN / General; DESIGN / Fashion; DESIGN / History & Criticism